2018
DOI: 10.1093/aobpla/ply007
|View full text |Cite
|
Sign up to set email alerts
|

Two closely related species differ in their regional genetic differentiation despite admixing

Abstract: Genetic differences between regions are usually studied for individual species. However, many species can reproduce with each other. We studied whether gene flow between two closely related sedge species influences regional differences. Our molecular genetic data support considerable gene flow between the species. Still, we detected clear genetic differences between species and regions, and more pronounced regional differences for the less common one. Thus, gene flow between the species appeared too weak to ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 92 publications
(146 reference statements)
0
5
0
Order By: Relevance
“…In small populations the effect of genetic drift could prevent local adaptation (Whitlock, 2003), as the ability to adapt may be compromised due to reduced genetic diversity (Pertoldi et al, 2007). We detected relatively high genetic diversity for C. viridula, despite its generally small population sizes (Schmidt et al, 2018) and we also found evidence for its adaptation to regional environments. Also for Arabis fecunda and Carlina vulgaris adaptation to local conditions was found despite small, isolated or fragmented populations (McKay et al, 2001;Becker et al, 2006).…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…In small populations the effect of genetic drift could prevent local adaptation (Whitlock, 2003), as the ability to adapt may be compromised due to reduced genetic diversity (Pertoldi et al, 2007). We detected relatively high genetic diversity for C. viridula, despite its generally small population sizes (Schmidt et al, 2018) and we also found evidence for its adaptation to regional environments. Also for Arabis fecunda and Carlina vulgaris adaptation to local conditions was found despite small, isolated or fragmented populations (McKay et al, 2001;Becker et al, 2006).…”
Section: Discussionmentioning
confidence: 54%
“…S1). We collected 572 genotypes from 43 natural populations of C. flava, C. viridula and C. x subviridula from those three regions, performed morphological and genetic differentiation analyses (Schmidt et al, 2017;Schmidt et al, 2018) and then propagated and transplanted cuttings of each genotype to pots in three gardens, one in each of the three regions. The regions differ in major environmental factors, including temperature, precipitation and day length.…”
Section: Introductionmentioning
confidence: 99%
“…The chloroplast genome is maternally inherited in angiosperm, having its own independent evolutionary route [6]. The chloroplast genome shows collinearity among the plant kingdom, which is why phylogenetic trees are constructed on the basis of chloroplast data, and the genome structure of chloroplast provides information regarding the specie origin, evolution, and also the differences between closely related and other species [7]. In recent years, with the advent of advanced sequencing technology, more chloroplast genomes have been sequenced [4].…”
Section: Introductionmentioning
confidence: 99%
“…Carex viridula is encountered both in calcareous, extremely and moderately rich fens, wet grasslands, and in very poor habitats such as dunes and sandy lake shores. Carex viridula frequently co-occurs with both C. lepidocarpa and C. flava, and much more seldom with C. demissa (Więcław 2014a,b) and hybridizes with all three mentioned species (Więcław and Wilhelm 2014;Schmidt et al 2018). Carex viridula is morphologically different from both C. flava and C. lepidocarpa, mainly in its much smaller utricles and shorter beaks, but is morphologically very close to C. demissa (e.g.…”
Section: Ecological Differentiation Within Closely Related Speciesmentioning
confidence: 99%